Shrinkage of body size in rodents as a strategy of populations under anthropogenic conditions (results of 50 years of study of rodent populations) - Мякушко, Станіслав Анатолійович (Національний науково-природничий музей НАН України, 2021)
Based on results of 50 years of continuous observations of populations of the pine vole (Microtus subterraneus de Selys-Longchamps, 1836) and yellow-necked wood mouse (Sylvaemus flavicollis Melchior, 1834), the phenomenon of reducing body size of individuals was revealed, particularly a significant reduction in body dimensions and body mass. The research was conducted at the Kaniv Nature Re-serve covering various stages of the local ecosystem's existence under anthropo-genic impact. Four cycles of density dynamics of two populations are chosen for comparison of their characteristics. The first three cycles correspond to qualitative-ly different periods in the existence of the protected ecosystem and populations of the studied species, whereas the last cycle reflects the current situation. It has been established that the tendency to decrease body dimensions is also characteristic for other rodent species, its manifestations are observed for 35 years, and the scale gradually increases. By fatness indexes, individuals of the pine vole on average lose 23.3% and yellow-necked wood mice lose 16.7% of the former values. It was shown that the level of reduce in exterior parameters is always greater in females than in males, and in the group of breeding adults it can reach 32%. It has been found that the phenomenon also applies to juveniles, whose fatness decreases by an average of 21%. The phenomenon occurs against the background of violations of various aspects of population dynamics, which allows it to be associated with anthropogenic changes in the environment. It is suggested that shrinking can be realized by various mechanisms. First, as a result of mortality, the largest individu-als and reproductive females with their greatest energy needs fall out of the popula-tion, and, second, the growth and weight gain of young animals is slower. As a result, the decrease in external parameters of individuals reduces their specific energy needs and allows them to better survive under adverse conditions. From these points of view, reducing body dimensions can be considered as a specific population strategy to maintain ecological balance.

На підставі безперервних 50-річних спостережень за популяціями полівки підземної (Microtus subterraneus de Selys-Longchamps, 1836) і миші жовтогрудої (Sylvaemus flavicollis Melchior, 1834) вияв-лений феномен здрібнення особин, який полягає у суттєвому зменшенні їх основних розмірно-масових показників. Дослідження проводили у Канівському природному заповіднику, а їх період охопив різні етапи існування екосистеми, обумовлені антропогенним впливом. У роботі для порівняння своїх харак-теристик обрані чотири цикли динаміки щільності двох популяцій. Перші три цикли відповідають якіс-но відмінним періодам в існуванні заповідної екосистеми і популяцій досліджуваних видів, а остан-ній — сучасній ситуації. Встановлено, що тенденція до здрібнення особин властива також іншим видам гризунів, його прояви спостерігаються упродовж 35 років, а масштаби поступово наростають. За вгодо-ваністю особини полівки підземної у середньому втрачають 23,3 %, а миші жовтогрудої — 16,7 % від колишніх значень. Показано, що зменшення екстер’єрних ознак самок завжди є більшим, порівняно з самцями, а у групі дорослих особин, що розмножуються, може досягати 32 %. Встановлено, що явище поширюється також на ювенільних осіб, вгодованість яких зменшується у середньому на 21 %. Явище відбувається на фоні порушень різних аспектів популяційної динаміки, що надає підстави пов’язувати його з антропогенними змінами середовища. Висунуте припущення, що здрібнення може реалізуватися за допомогою різних механізмів. По-перше, у результаті смертності із популяції випадають найкрупніші особини і репродуктивні самки з їхніми найбільшими енергетичними потребами, по-друге, повільніше відбувається ріст і набір маси молодими тваринами. У кінцевому результаті зменшення екстер’єрних параметрів особин зменшує їх питомі енергетичні потреби і дає можливість краще переживати несприя-тливі умови. З цих позицій здрібнення своїх елементів можна розглядати у якості специфічної популя-ційної стратегії щодо підтримання екологічного балансу.
Здрібнення особин як стратегія популяцій в антропогенних умовах (досвід 50-річного вивчення популяцій гризунів)
Keywords: reduced body size; population dynamics; forest-dwelling rodents; ecological balance; здрібнення; динаміка популяцій; лісові гризуни; екологічний баланс